2001
DOI: 10.1038/35071095
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the mammalian node requires Arkadia function in the extraembryonic lineages

Abstract: The early mammalian embryo is patterned by signals emanating from extraembryonic and embryonic signalling centres, most notably the anterior visceral endoderm (AVE) and the node, respectively. The AVE is responsible for anterior development, whereas further axis specification depends on the node, the equivalent of Spemann's organizer. Formation of the node, at the anterior primitive streak, depends on expression of the transcription factor HNF3beta (ref. 4). However, both the source and the nature of the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 28 publications
2
93
0
Order By: Relevance
“…As Cer1 and Leftb are Nodal antagonists, and Drap1 is probably a transcriptional corepressor for Nodal, these defects appear to be a consequence of increased levels of Nodal signaling. In support of this idea, mutant embryos with the loss-of-function of two Nodal signaling modulators, Foxh1 and arkadia (Rnf111 -Mouse Genome Informatics), fail to establish an anterior primitive streak/node and its derivatives (Hoodless et al, 2001;Yamamoto et al, 2001;Episkopou et al, 2001). Finally, either conditional loss-of-function of Smad2, a Nodal effector, in the epiblast or decreased Nodal signals in the primitive streak results in a specific loss of the ADE and prechordal mesoderm (Vincent et al, 2003).…”
Section: Lrp5 and Lrp6 Have Redundant Functions During Embryonic Devementioning
confidence: 85%
“…As Cer1 and Leftb are Nodal antagonists, and Drap1 is probably a transcriptional corepressor for Nodal, these defects appear to be a consequence of increased levels of Nodal signaling. In support of this idea, mutant embryos with the loss-of-function of two Nodal signaling modulators, Foxh1 and arkadia (Rnf111 -Mouse Genome Informatics), fail to establish an anterior primitive streak/node and its derivatives (Hoodless et al, 2001;Yamamoto et al, 2001;Episkopou et al, 2001). Finally, either conditional loss-of-function of Smad2, a Nodal effector, in the epiblast or decreased Nodal signals in the primitive streak results in a specific loss of the ADE and prechordal mesoderm (Vincent et al, 2003).…”
Section: Lrp5 and Lrp6 Have Redundant Functions During Embryonic Devementioning
confidence: 85%
“…Genetic evidence in mice favors a role for Arkadia because Arkadia-null mutant embryos succumb to severe gastrulation defects due to impaired Nodal/Smad2/3 signaling (Episkopou et al 2001;Mavrakis et al 2007). One interpretation of this phenotype is that in the absence of Arkadia, SnoN associates with crucial Nodal/Smad2/3 target genes, preventing their activation.…”
Section: Snon Occupies Sbes In Mesendodermal Genesmentioning
confidence: 99%
“…Other genes, such as Lim1, Otx2,Nodal,Smad2,Foxh1,Arkadia,Hex,Oto,Dkk1,Hesx1, Nog and Chrd, are also essential for murine head development (Episkopou et al, 2001;Hoodless et al, 2001;Shawlot et al, 1999;Yamamoto et al, 2001). However, the brain defects are considerably different among these mutants.…”
Section: Cnbp Appears To Regulate Cell Proliferation and Tissue Specimentioning
confidence: 99%
“…Similarly, gene knockout techniques have proved to be powerful tools for identifying the molecular regulation of many developmental processes. For example, genes such as Lim1 (Lhx1 -Mouse Genome Informatics) (Shawlot and Behringer, 1995), Otx2 (Matsuo et al, 1995;Acampora et al, 1995), Smad2 (Waldrip et al, 1998;Nomura and Li, 1998), Nodal , Foxh1 (Hoodless et al, 2001;Yamamoto et al, 2001), Arkadia (Episkopou et al, 2001), Hex (Martinez Barbera et al, 2000), Oto (Zoltewicz et al, 1999), Hesx1 (Dattani et al, 1998) and Dkk1 (Mukhopadhyay et al, 2001;Shawlot et al, 1999;Yamamoto et al, 2001) have been demonstrated to be essential for normal head development by targeted gene disruption in mice. However, studies using such knockout techniques are limited to known genes.…”
Section: Introductionmentioning
confidence: 99%